The role of telenursing in the management of diabetes：A systematic review and meta‐analysis. Issue 4 (18th March 2019) - Yang, Sa; Jiang, Qiuhuan; Li, Hongfang
Abstract: Background: Diabetes is a common chronic disease that requires a long‐term regimen. However, the management of diabetes by telenursing is limited and inconclusive. Objectives: To determine the effectiveness of telenursing on control in diabetes. We conducted a systematic review and meta‐analysis of randomized controlled trials (RCTs). Methods: We searched electronic databases, including PubMed, Embase, Web of Science and Cochrane Library. Studies comparing telenursing with usual care in diabetes patients were included. Results: A total of 17 randomized controlled trials were identified. Glycated hemoglobin (HbA1c) dates were pooled using a random effects meta‐analysis method, followed by subgroup analyses to examine heterogeneity. The meta‐analysis showed that the use of telenursing (vs. usual care) was associated with a significant reduction in HbA1c levels compared to usual care, with a pooled 0.68% (95% CI: 0.33–1.03, p = 0.0001; I 2 = 95%). For the secondary outcome, the SMD of body mass index (BMI) was −0.25% (95% CI: −0.81 to 0.32%, p = 0.39), with no statistically significant change; the fasting blood sugar (FBS) SMD was −0.19% (95% CI: 0.20 to 1.01, p = 0.003), with a statistically significant change; the total cholesterol (TC) SMD was −0.09% (95% CI: −0.03 to 0.21, p = 0.12), with no statistically significant change. Conclusions: Telenursing, as a useful tool for patient education and behavioral interventions, can help diabetes patients to improve their glycemic control. However, more studies on up‐to‐date and cost‐effective technologies are needed.